Stability analysis of different biostimulant applications to flowering characters of rose (Rosa hybrida) cultivar First Red - GUPTA, Y C; GUPTA, R K; MOONA, MOONA; DHIMAN, S R (The Indian Journal of Agricultural Sciences, 2012)
Stability parameters were estimated for four quantitative flowering characters of rose cultivar First Red under 22 biostimulant applications during two years and two seasons in each year, i e 2006–07 and 2007–08 by using Eberhart and Russel’s model (1966). All analysis of variance showed that biostimulants had significant responses towards different environment changes. Significant biostimulant × Environment interactions were detected for all the four characters, i e number of flowering shoots/plant, flower bud length, days taken from bud appearance to harvesting of rose and flower size. Winter season were found to be suitable for days taken from bud appearance to harvesting of last flower and flower size as compared to summer season. Treatment 16 (i e 50% recommended dose of NPK+5% Panchagavya + 5 % Manchurian mushroom tea) were found to be stable biostimulant for two characters, i e number of flowering shoot/plant and flower size.